1992
DOI: 10.1111/j.1365-3032.1992.tb01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod and temperature on the termination of diapause in the univoltine seed wasp Eurytoma plotnikovi

Abstract: Mummified pistachios containing fully grown diapause larvae of Eurytoma plotnikovi Nikol'skaya (Hym., Eurytomidae) were collected in early August and late September in coastal northern Greece and subjected to various photoperiod and temperature treatments, then maintained at 19 or 26°C and a long‐day (LD 16:8 h), a changing, or a short‐day (LD 10:14 h) photoperiod until pupation. In larvae of early August (beginning of diapause) subjected for 20 weeks to 19°C under a long, a changing, or a short photophase, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
2
18
1
Order By: Relevance
“…Even by the 14th day under the above laboratory condition only 64 to 75% of the larvae pupated. Subsequent work already publish ed, with larvae from the same orchard, has shown that after larvae are exposed to short days and low temperature, as was the case with larvae of the present experiment, pupation takes place much sooner under long days than under short days (Tzanakakis et al 1992). We do not know whether the delayed termination of diapause in the caged fruits was due to differences in photoperiod, in temperature, or in both from those on the trees.…”
Section: Diapause Termination In the Fieldmentioning
confidence: 89%
See 3 more Smart Citations
“…Even by the 14th day under the above laboratory condition only 64 to 75% of the larvae pupated. Subsequent work already publish ed, with larvae from the same orchard, has shown that after larvae are exposed to short days and low temperature, as was the case with larvae of the present experiment, pupation takes place much sooner under long days than under short days (Tzanakakis et al 1992). We do not know whether the delayed termination of diapause in the caged fruits was due to differences in photoperiod, in temperature, or in both from those on the trees.…”
Section: Diapause Termination In the Fieldmentioning
confidence: 89%
“…The present work preceded that by Tzanakakis et al (1992), which was carried out with larvae taken two years later from the same trees. There fore, the photoperiod and temperature combin ations we used were not planned to complement that work.…”
Section: Diapause Termination Under Laboratory Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This wasp has at least two diapause stages or phases. In the laboratory, larvae collected in early August completed the first stage more rapidly under a short-day and low temperature conditions, and the second stage more rapidly under a long-day and high (26°C) to mildly high (19°C) temperature conditions (Tzanakakis et al, 1992).…”
Section: Low Temperature Applied After a Period Of 20°cmentioning
confidence: 99%